Metode Pembelajaran Pembentukan Karakter dalam Perspektif Teori Perilaku Organiasi : Studi Kasus di Sekolah Alam SD Fathia - Fatimah Nurjariah; Kun Nurachadijat (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
Natural school is an alternatve school regarding the school system with the concept of universe-based education. One of the strategies for building alternative education is to organize a factual and conceptual learning processes, orgenaize education with educational enviromental conditions, organize environment-based learning processes, orgenaize learning that build cognitive, affective and psychomotor abilities, foster creative, and so on. The idea of this natural school was initiated by Lendo Novo based on his concern that the cost of education which is increasingly out of reach for the community. To get to know natural school, the author conducted a mini research into a natural school in the city Sukabumi, namely SD Islam Alam Fathia which is located at Ciberuem Sukabumi City, West Java. This study aims to determine the Character-buliding, learning method inn the perspective of organizational behavior theory at SD Fathia’s natural School. The method used in this research is descriptive qualitative methode. Where the researcher tested the validity of the data by triangulation of sources, namely by conducting interviews, observation and documentation. The finding of this study. Researchers found a new concept in learning, namely by learning with nature and making nature a medium for unlimited creativity for children. School such us the Alam Fatihia Islamic Elementary School are school that are indeed being sought by paraents, in order to make their children knowleadgeable and have character based on faith, science and nature.